2021
DOI: 10.1021/acs.orglett.1c01716
|View full text |Cite
|
Sign up to set email alerts
|

C–H Alkylation of Aldehydes by Merging TBADT Hydrogen Atom Transfer with Nickel Catalysis

Abstract: Catalyst controlled site-selective C−H functionalization is a challenging but powerful tool in organic synthesis. Polarity-matched and sterically controlled hydrogen atom transfer (HAT) provides an excellent opportunity for site-selective functionalization. As such, the dual Ni/photoredox system was successfully employed to generate acyl radicals from aldehydes via selective formyl C−H activation and subsequently cross-coupled to generate ketones, a ubiquitous structural motif present in the vast majority of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Since recent work used a light wavelength of ca. 390 nm for decatungstateanion-catalyzed reactions [29][30][31][32]. We also tested other wavelengths of 385 and 395 nm for the irradiation of decatungstate catalyst and the reactions also proceeded well to give almost the same results compared as for irradiation at 365 nm (Table 1, entry 7 and 8).…”
Section: Resultsmentioning
confidence: 94%
“…Since recent work used a light wavelength of ca. 390 nm for decatungstateanion-catalyzed reactions [29][30][31][32]. We also tested other wavelengths of 385 and 395 nm for the irradiation of decatungstate catalyst and the reactions also proceeded well to give almost the same results compared as for irradiation at 365 nm (Table 1, entry 7 and 8).…”
Section: Resultsmentioning
confidence: 94%
“…Control experiments revealed that no desired product was formed in the absence of either Ni-precatalyst (entry 14) or TBADT (entry 15), confirming the synergistic effect of these two catalysts. Moreover, the reaction was nearly or completely shut down when it was carried out without a base or light (entries [16][17].…”
Section: Resultsmentioning
confidence: 99%
“…[15] Very recently, a similar protocol describing the cross-coupling reaction of aldehydes with benzylic and allylic Katritzky salts via CÀ N bond cleavage was reported by Rasappan and coworkers. [16] As a part of our ongoing studies in this research field, we demonstrate herein the accomplishment of acyl CÀ H benzylation of aldehydes with primary and secondary benzyl chlorides under the cocatalysis of nickel and TBADT (Scheme 1B).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…To establish a new strategy for the C­(sp 2 )–H allylation of a formyl moiety, we turned our attention to the cooperative catalysis of nickel and tetrabutylammonium decatungstate (TBADT), which has been applied in cross-coupling reactions involving hydrocarbons or aldehydes. In our hypothesis, the hydrogen-atom-transfer (HAT) photocatalyst TBADT promotes radical-type umpolung of aldehydes or formamides via homolytic acyl C–H bond cleavage under irradiation, whereas low-valent nickel interacts with electrophilic allyl alcohols or their derivatives to form a π-allylnickel intermediate . The following coupling of these two species generated by distinct catalysts would provide novel access to β,γ-unsaturated ketones or amides (Scheme B).…”
mentioning
confidence: 99%